1974
DOI: 10.4102/koedoe.v17i1.906
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the African Elephant on the vegetation of the Addo Elephant National Park

Abstract: <!-- @page { margin: 2cm } P { margin-bottom: 0.21cm } --> <p style="margin-left: 1.22cm; margin-bottom: 0cm;" lang="en-US" align="justify"><span style="font-size: x-small;">An increasing elephant <em>Loxodonta africana</em> population has been confined to a 2 770 ha enclosure since 1954. When compared to the vegetation adjacent to the enclosure, the plant biomass within has been reduced by more than one half. Changes in the botanical composition are described.</span></p&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 0 publications
0
42
0
Order By: Relevance
“…Consequently, there is a dearth of comparative data against which to evaluate the results of this study. Penzhorn et al (1974) undertook destructive sampling of 10 protected and 10 open plots in the Xeric Succulent Thicket of Addo Elephant National Park (approximately 100 km west of the study site) and recorded a mean total (including wood, twigs and leaves) fresh biomass of 184733 t ha À1 and 8578 t ha À1 in the protected and open areas, respectively. This would equate to between 45 and 97 t ha À1 dry mass.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is a dearth of comparative data against which to evaluate the results of this study. Penzhorn et al (1974) undertook destructive sampling of 10 protected and 10 open plots in the Xeric Succulent Thicket of Addo Elephant National Park (approximately 100 km west of the study site) and recorded a mean total (including wood, twigs and leaves) fresh biomass of 184733 t ha À1 and 8578 t ha À1 in the protected and open areas, respectively. This would equate to between 45 and 97 t ha À1 dry mass.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the impact of elephant browsing on tall single-stemmed aloes have shown that there is generally a higher proportion of dead aloes at sites where elephants are present than control sites where they are absent Bernard, 2008, 2009;Penzhorn et al, 1974). Elephants either break off the aloe's crown, or push the whole plant over to access the succulent apical meristem, both of which usually result in plant death (Parker and Bernard, 2009).…”
Section: Single-stemmed Aloesmentioning
confidence: 96%
“…In AENP, the elephant density has consistently exceeded the recommended stocking rates (Pentzhorn et al 1974, Boshoff et al 2002 as managers assume that tourists require high densities to achieve game-viewing satisfaction (Novellie 1991). This has been accompanied by substantial impacts on biodiversity (reviewed by Kerley and Landman 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One recommendation is that densities in the AENP should not exceed 0.4 elephant/ km 2 (Pentzhorn et al 1974), and Boshoff et al (2002) There is thus a need to provide managers with insights as to how many elephants are required to achieve tourist satisfaction, while keeping numbers low enough to ensure that protected areas adequately fulfil their function of conserving biodiversity. We tested the hypothesis that high elephant densities are needed for tourist satisfaction and that increased elephant densities thereby increase tourist numbers (Novellie 1991).…”
Section: Introductionmentioning
confidence: 99%